2022
DOI: 10.3390/cells11071117
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Action of Extracorporeal Photopheresis in the Control of Bronchiolitis Obliterans Syndrome (BOS): Involvement of Circulating miRNAs

Abstract: Clinical evidence suggests an improvement or stabilization of lung function in a fraction of patients with bronchiolitis obliterans syndrome (BOS) treated by extracorporeal photopheresis (ECP); however, few studies have explored the epigenetic and molecular regulation of this therapy. The aim of present study was to evaluate whether a specific set of miRNAs were significantly regulated by ECP. Total RNA was isolated from serum of patients with established BOS grade 1–2 prior to the start and after 6 months of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Following our previous results on the levels of circulating miRNAs [ 12 ], in order to define if ECP effects are mediated by modulation of MNCs in term of differential miRNA expression and release. The present study represents an extension of the previous one [ 12 ] and it regard patients subjected to ECP using the off-line method at the Apheresis Unit of the Immunohaematology and Transfusion Service of our hospital.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following our previous results on the levels of circulating miRNAs [ 12 ], in order to define if ECP effects are mediated by modulation of MNCs in term of differential miRNA expression and release. The present study represents an extension of the previous one [ 12 ] and it regard patients subjected to ECP using the off-line method at the Apheresis Unit of the Immunohaematology and Transfusion Service of our hospital.…”
Section: Resultsmentioning
confidence: 99%
“…For the present study, we selected four miRNAs previously identified as being associated with BOS and/or ECP response in serum [ 12 ] and miRNAs previously reported in proliferation and function regulation of the main immune cell types of the innate and adaptive immunity [ 15 , 16 ]. In particular, we investigated the relative expression of hsa-miR-155-5p, hsa-miR-146a-5p, hsa-miR-31-5p, hsa-miR-181a-3p, hsa-miR-16-5p, hsa-miR-142-3p and hsa-miR-23b-5p, reported to be involved in the regulation of DCs, B ad T cell immunosoppressive properties.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the disease progresses or worsens despite treatment, retransplantation remains the ultimate necessary option for BOS. [49] 3) Risk factors for BO. Hypoxemia, mechanical ventilation, shortness of breath, and wheezing are the main risk factors for PIBO.…”
Section: Hotspots and Frontiersmentioning
confidence: 99%
“…Recently, the alteration of Smad-4 has been found in association with miR-155-5p and miR-23b-3p, which resulted in an altered expression in responders to extracorporeal photopheresis [ 141 ].…”
Section: Extracellular Vesiclesmentioning
confidence: 99%